Integrating Educational Philosophy into the Development of Islamic Education Practices in the Modern Era - Aini, Nurul; Sassi, Komarudin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine the integration of educational philosophy in the development of Islamic education practices in the modern era, characterized by social, cultural, and technological changes. Islamic education is not only focused on knowledge transfer but also on the cultivation of moral character and holistic personality development. However, global dynamics require a new paradigm that can uphold core Islamic values while remaining adaptive to contemporary generational needs. This study employs a qualitative descriptive-analytical approach through literature review and contextual analysis. Data were collected from educational philosophy literature—including Perennialism, Essentialism, Progressivism, Existentialism, Reconstructionism, Pragmatism, Constructivism, Idealism, and Realism—as well as the thoughts of prominent Islamic education scholars. Analysis was conducted by relating philosophical ideas to Islamic educational principles emphasizing the integration of faith, knowledge, and practice. The results indicate that Islamic education should combine timeless values aligned with Perennialism and Idealism with adaptive approaches offered by Progressivism, Constructivism, and Reconstructionism. This integration strengthens spiritual, intellectual, and life skills while fostering critical, creative, and collaborative thinking. Thus, Islamic education functions not only as a preserver of scholarly tradition but also as a transformative, solution-oriented, and globally competitive force